Recicladores de base en América Latina: un estudio de caso comparativo entre São Paulo y Ciudad de México - Izidoro, Leila Giovana (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2021)
Since the 1970s, international financial organizations started to promote the implementation of the integrated solid waste management model in Latin America. Through public-private partnerships, this model aims to exploit energy resources in landfills and to sell recyclables in reverse logistics chains. Waste pickers, workers who survive from collecting, sorting, and selling recovered materials, were impacted by these initiatives, through their expulsion from open dumps, the criminalization of their presence on the city’s streets and the gradual regulation of their work. Thus, this article aims to identify these impacts on the conformation of the workforce of waste pickers in Latin America, based on a comparative case study between the cities of São Paulo and Mexico City. For this, literature review, semi-structured interviews and fieldwork carried out between 2019 and 2021 in both cities were used as research sources. From the data mobilized here, it was concluded that, despite the different processes of insertion of waste pickers in the integrated solid waste management system and the regulation of their work, in both cities the exploitation of their labor power has been carried out in the most beneficial way for capital, from subcontracting networks encouraged by the State, in partnership with companies.